Insertion Reaction of 2-Halo-N-allylanilines with K2S Involving Trisulfur Radical Anion: Synthesis of Benzothiazole Derivatives under Transition-Metal-Free Conditions - Liu, Xin-Yu; Zhao, Yan-Wei; Jiang, Tian; Rao, Weidong; Wang, Shun-Yi (Synthesis, 2020)
A synthesis of benzothiazole derivatives through the reaction of 2-halo-N-allylanilines with K2S in DMF is developed. The trisulfur radical anion S3·–, which is generated in situ from K2S in DMF, initiates the reaction without transition-metal catalysis or other additives. In addition, two C–S bonds are formed and heteroaromatization of benzothiazole is triggered by radical cyclization and H-shift.
Keywords: transition metal-free; trisulfur radical anion; benzothiazole derivatives; radicals; cyclization